Análisis y puesta en valor del patrimonio cultural inmaterial del cantón Olmedo con fines turísticos - Cuenca Buri, Yessenia Elizabeth (2018)
Abstract:The intangible cultural heritage forms part of the cultural heritage, where the community is responsible for maintaining and preserving the cultural diversity of its people, as mentioned, the present work describes the process of analysis and enhancement of the intangible cultural heritage of the canton Olmedo to consider and valuate how important the PCI is. For the investigation several theories were considered, and for a better understanding of the subject to be treated as: heritage, tourism and inventory. Like the legal framework that provides an adequate management of intangible heritage. An analysis identifies the attractions present in the community, such as tangible and intangible resources, which together with the information collected through surveys and Focus Group workshops contributed to the execution of the tourism proposal reflected in a web page that focuses on the recognition and preservation of intangible cultural heritage among the population of the Olmedo canton, which is still preserved today. Finally, the conclusions and recommendations are presented to give a clear view of this writing.